THE IMPORTANCE OF THE MEMOIRS OF AMBASSADOR DUNG WANG – IN THE STUDY OF THE HISTORY OF FERGANA OF THE EPHTHALITE PERIOD (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
Based on historical sources and literature, the article covers the first visit of the Chinese ambassador Dung Wan to the Fergana Valley. This ambassador provides important information about the state of Ferghana and its political situation in the 40s of the 5th century. About the period of the Ephthalites, one of the least researched periods of the history of Ferghana, the dates of the Hephthalites' annexation of the valley to their state were clarified, and the relationship with the local dynasty was discussed. Information about the establishment of the Yaipan khanate, its territory, and the customs of its inhabitants is provided.